Effects of Management Accounting Practices on SME Performance in Bangladesh: A Study of Southern Region of Bangladesh - Md. Faykuzzaman Mia (Global Journal of Management and Business Research, 2023)
The following article emphases on determining the effects of Management Accounting Practices on Small and Medium sized Enterprises SME The SMEs studied in the research belong to the southern part of Bangladesh including Faridpur Madaripur Bagherhat Khulna and Gopalganj Quantitate research approach has been used and data was collected from 252 SME managers by using a well-structured questionnaire The sample was selected through random sampling methods SPSS Statistical Package for the Social Science update version was used to analysis the data The article has introduced multiple regression analysis to identify the relationship between management accounting practices and business performances of an organization Multiple regressions analysis has been used to measure the impact of the relationship in the research model The results of regression analysis showed that a positive relationship was exited between management accounting practices and SMEs business performance These applied studies explore the impact of management accounting practices on SME business and play a useful role to the academicians by creating a significant contribution in future research in this field within in Faridpur Madaripur Bagherhat Khulna and Gopalganj five districts of southern region of Bangladesh In concluding remarks included which reflects the MAPs have an impact on the performance of an organization and how the study help to improve the MAPs that positively influenced the performance of SMEs